Designing ultrathin Fe doped Ta2O5-x nanobelts for highly enhanced ammonia photosynthesis - Xin, Changhui; Sun, Hezheng; Yao, Jiaxin; Wang, Bin; Yu, Xin; Tang, Yanting (Journal of colloid and interface science, 2024)
[Display omitted] •Ultrathin Fe-Ta2O5-x nanobelts were fabricated.•Fe-Ta2O5-x nanobelts showed highly improved surface areas and solar-light harvesting.•Fe doping induced the decreased working function and formation of more oxygen vacancies.•Fe-Ta2O5-x nanobelts exhibited highly enhanced photocatalytic performance. Solar-light photosynthesis of ammonia form N2 reduction in ultrapure water over the artificial photocatalysts is attractive but still challenging compared with Haber–Bosch process. In this work, ultrathin Fe-Ta2O5-x nanobelts were fabricated via the controllable solvothermal process for ammonia photosynthesis. The formed oxygen vacancies and Fe doping narrowed their bandgap energies and promoted the carriers’ separation and transfer for Fe-Ta2O5-x nanobelts. In addition, Fe doping also resulted in the reduced working functions of the samples, indicating a weaker electron binding restriction and stronger separation and transfer of photo-induced carriers. The experimental results showed that Fe-Ta2O5-x nanobelts showed remarkably enhanced photocatalytic ammonia production performance under simulated sunlight irradiation, and the relevant ammonia production rate reached approximately 3030.86 μM g−1 h−1, which was 9.63 times of pristine Ta2O5-x and 491.0 times of commercial Ta2O5, and a relatively stable photocatalytic ammonia production performance under simulated sunlight irradiation for Fe-Ta2O5-x nanobelts. Meanwhile, it was also found that Fe doping has great influences on the photocatalytic performance under visible light and simulated sunlight irradiation, mainly because of their suitable bandgap energies and enhanced solar-light harvesting capacity. Current work indicates the great potentials of ultrathin tantalum-based functional materials for high-efficiency ammonia photosynthesis.